Cyberbole. - Blume, Harvey (American Prospect)
The writer discusses Jaron Lanier's One Half of a Manifesto, which is not dedicated to proclaiming a new theory, as most manifestos are, but to deflating the already fully-formed theory of cybernetic totalism. This theory, developed by an elite group of techies, is one of those grandiose ideologies that attempts to explain everything. In his 9,000-word document, Lanier argues that cybernetic totalism is primed to wreak havoc on the world. Lanier, sets out to oppose some of the most formidable writers and theorists of the present time. He is not a defector from the digital revolution that he has helped to foment, but he does join in the postmillennial mood of second thoughts about computers and the Internet from a philosophical perspective. Lanier is determinedly anti-totalism, and he argues that the totalism to be most wary of at present is built on Darwinism. Darwinism provides the new totalists with what they take to be a bridge between nature and technology and a way to translate between genetics and cybernetics. Lanier's warns of the horrors ahead when the computer becomes instrumental in human genetic engineering.